Reality of Using Artificial Intelligence in Teaching Primary School Students in Damascus from the Perspectives of their Teachers (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of this research is to shed light on teachers' attitudes towards the experience of composing curricula for music education in the Syrian Arab Republic, which may contribute to identifying the pros and cons of this experience and the difficulties that encountered composing and implementing curricula. It can provide solutions to overcome these difficulties in order to keep pace with the changes that have taken place in all areas of life in general, and in the educational field in particular, and to include all stages of education, including the first cycle of the basic education stage.The research deals with an important issue in the field of education, as it can, through its results, clarify the picture that music education teachers have about the effectiveness of their curricula in teaching music, and thus provide decision makers and specialists in the Ministry of Music Education with important information about the reality of this experience.At the end of his research, the researcher presented a set of results that he had drawn, and based on that he recommended a set of recommendations related to the subject of the research.Including continuing to develop the curriculum project continuously. Diversification of the members of the committees from assistant teachers, teachers and graduate studies. And take advantage of parents' directions because they are partners in the educational process.
Keywords: Teachers; Music